Deciding the Rank of Factors Affecting Abu Dhabi Oil & Gas Industry - Al Mansoori, Fatima Taher; Abdul Rahman, Ismail; Kasim, Rozilah (International Journal of Sustainable Construction Engineering and Technology, 2020)
This paper presents the ranking of factors affecting Abu Dhabi oil & gas industry which involved 100 valid responses. The respondents were requested to rate 25 identified factors which are clustered into five groups using 5-point Likert scale with scale 5 for extremely significant to scale 1 for not significant. The data collected from the survey was analysed descriptively using mean score index and standard deviation. The findings of the ranking analysis show the five most significant factors affecting the performance in the oil & gas industry are Rewards and recognition, Low employee turnover, Effective behaviour, Assuring job security, and Effective support system. These findings are useful for further investigation on the factors affecting performance in oil & gas industry.